3′-Azido-3′-deoxythymidine (AZT) inhibits thymidine phosphorylation in isolated rat liver mitochondria: A possible mechanism of AZT hepatotoxicity - Lynx, Matthew D. (2006)
3′-Azido-3′-deoxythymidine (AZT) is a staple of highly active antiretroviral therapy (HAART). Prior to HAART, long-term use of high-dosage AZT caused myopathy, cardiomyopathy, and hepatotoxicity, associated with mitochondrial DNA depletion. As a component of HARRT, AZT causes cytopenias and lipodystrophy. AZT-5′-triphosphate (AZTTP) is a known inhibitor of the mitochondrial polymerase γ and has been targeted as the source of the mitochondrial DNA depletion. However, in previous work from this laboratory with isolated rat heart mitochondria, AZT phosphorylation beyond AZT-5′-monophosphate (AZTMP) was not detected. Rather, AZT was shown to be a more potent inhibitor of thymidine phosphorylation (50% inhibitory concentration (IC(50)) of 7.0 ± 1.0 μM) than AZTTP is of polymerase γ (IC(50) of >100 μM), suggesting that depletion of mitochondrial stores of TTP may limit replication. This work has investigated whether an identical mechanism might account for the hepatotoxicity seen with long-term use of AZT. Isolated rat liver mitochondria were incubated with labeled thymidine or AZT, and the rate and extent of phosphorylation were determined by HPLC analysis of acid-soluble extracts of the incubated mitochondria. The results showed that in the phosphorylation of thymidine to TMP, liver mitochondria exhibit a higher V(max) and K(m) than heart mitochondria, but otherwise heart and liver mitochondria display similar kinetics. AZT is phosphorylated to AZTMP, but no further phosphorylated forms were detected. In addition, AZT inhibited the production of TTP, with an IC(50) of 14.4 ± 2.6 μM AZT. This is higher, but comparable to, the results seen in isolated rat heart mitochondria.